(untitled) (Eurasian Journal of Engineering and Technology, 2023)
We can say that high-quality steel alloy is being liquefied in an electric arc furnace, first of all, the chemical composition of low-carbon steel alloy has been developed, and solidified steel has been obtained. Then, in the process of fluidization, it was possible to obtain high-quality steel zagatovka by introducing different types of flux into the alloy. The heat provided for the main fluidization of the furnace can cause a large amount of burn from fine solids when the furnace electrodes are lowered. For this reason, the order of loading the slag into the furnace was developed, and it was achieved to reduce the amount of slag burning